Teacher Motivation as a Factor in Language Teaching and Learning in Nigeria - Christopher, Nkechi M (Journal of NELTA, 2013)
A survey was carried out to investigate the level of teacher motivation, the association between teacher motivation and language learning and teaching, as well as the factors that could impact on them in two states in the Nigeria federation. This study became necessary in order to assess the impact that government efforts, particularly the use of salary incentives, have made in restoring standards in the school system. The view is held that there has been no commensurate improvement in student performance in response to government’s gesture. However, this study indicates that most teachers are more intrinsically than extrinsically motivated in their exhibition of commendable classroom behaviours. Teachers’ claim that they are not motivated to teach is supported by negative assessment of several variables in the teaching/learning environment that are critical in raising and maintaining teacher motivation, teaching efficiency and effective language learning. Journal of NELTA, Vol. 17 No. 1-2, December 2012, Page 14-25 DOI: http://dx.doi.org/10.3126/nelta.v17i1-2.8089